PENGARUH DIGITALISASI TERHADAP TUMBUH KEMBANG KARAKTER ANAK DI SD PELANGI KASIH BOGOR - Louwise, Sandra; Lie, Romi (JURNAL KADESI, 2024)
The increasingly rapid growth of digitalization has had a very significant impact on all groups, including elementary school children. Since the age of toddlers, children have been exposed to digitalization through gadgets introduced by their parents. Even though their hands are still too small and weak to be able to hold gadgets. The introduction of gadgets too early has affected children's psychology. Therefore, the aim of this research is to find out how much influence digitalization has on the growth and development of children's character, especially children at Pelangi Kasih Elementary School, Bogor. This research uses quantitative research methods with data obtained through questionnaires, interviews and direct observations of students during class. The questionnaire data source was taken from a class 6 sample of 30 children out of a total of 160 children. Meanwhile, interviews were conducted with conversations with parents and guardians of grade 6 students, either directly or indirectly, via telephone or via WhatsApp messages. Finally, the researcher made direct observations of students during class. The data sources obtained are then analyzed to produce research. The research results show that digitalization has indeed had a negative and positive influence on the character growth and development of children at Pelangi Kasih Elementary School, Bogor. Bad character and traits are inherent in children who use digitalization incorrectly and are supported by parents who give them freedom when playing with gadgets. Meanwhile, good character and traits are inherent in children who use digitalization properly and are supported by parents who set limits when playing with gadgets. The role of parents determines the formation of children's character and traits.